Intravenous Esomeprazole for Prevention of Peptic Ulcer Rebleeding: A Randomized Trial in Chinese Patients. Issue 11 (November 2015) - Bai, Yu; Chen, Dong-Feng; Wang, Rong-Quan; Chen, You-Xiang; Shi, Rui-Hua; Tian, De-An; Chen, Huifang; Eklund, Stefan; Li, Zhao-Shen
Abstract Introduction High-dose intravenous esomeprazole is the only approved pharmacological treatment for the prevention of peptic ulcer rebleeding (currently approved in over 100 countries worldwide), but has not yet been approved in China. This study aimed to evaluate a high-dose esomeprazole intravenous regimen vs. an active control (cimetidine) for the prevention of rebleeding in Chinese patients with a high risk of peptic ulcer rebleeding who had undergone primary endoscopic hemostatic treatment. Methods This was a parallel-group study conducted at 20 centers in China. The study comprised a randomized, double-blind, intravenous treatment phase of 72 h in which 215 patients received either high-dose esomeprazole (80 mg + 8 mg/h) or cimetidine (200 mg + 60 mg/h), followed by an open-label oral treatment phase in which all patients received esomeprazole 40 mg tablets once daily for 27 days. The primary outcome was the rate of clinically significant rebleeding within the first 72 h after initial endoscopic hemostatic therapy. Secondary outcomes included the rates of clinically significant rebleeding within 7 and 30 days; proportions of patients who had endoscopic retreatment and other surgery due to rebleeding; and number of blood units transfused. Results The rate of clinically significant rebleeding within 72 h was low overall (3.3%) and numerically lower in patients treated with esomeprazole compared with cimetidine (0.9% vs. 5.6%). Overall, the results of the secondary outcomes also showed a numerical trend towards superiority of esomeprazole over cimetidine. All treatments were well tolerated. Conclusion In this phase 3, multicenter, randomized trial conducted in China, esomeprazole showed a numerical trend towards superior clinical benefit over cimetidine in the prevention of rebleeding in patients who had successfully undergone initial hemostatic therapy of a bleeding peptic ulcer, with a similar safety and tolerability profile. These findings suggest that esomeprazole may be an alternative treatment option to cimetidine for this indication in China. Funding AstraZeneca. Trial registration ClinicalTrials.gov identifier, NCT01757275.